The Status of Indonesia’s E-Procurement - Achmad Nurmandi (Jurnal Studi Pemerintahan, 2013)
E-procurement is an important intrument to prevent corruption in goods and services procurement budget. Indonesia has been implementing the e-procurement project since 2008 based on Presidential Decree. President has stipulating annual order (presidential instruction) has to be obey by all ministries and local governments to procure their budget through r-procurement mechanism. However, untill 2012 fiscal year, this research found that only around 10.26% of central government institution procurement budget, including ministries and 21,10% of local government procurement budget did procure through e-procurement method. This research concluded that regulation, leadership and procurement intitution are challanging factors to make “status quo” e-procurement.